A beginner's guide to PROTACs and targeted protein degradation. (1st October 2021) - Ciulli, Alessio; Trainor, Nicole
Abstract : Those with a keen interest in targeting proteins, from chemical biologists to drug hunters alike, cannot help but take notice that a new type of molecule is making waves across this research space. Proteolysis Targeting Chimeras (or PROTACs) are protein degraders, which utilize the cell's own waste disposal machinery to eliminate instead of inhibit a target protein. The key to PROTACs is their bifunctionality: they simultaneously bind a target protein and an E3 ligase protein, which then ubiquitylates the target, marking it for proteasomal degradation. This concept originated in the late 1990s and the first PROTAC was reported in 2001 by the laboratories of Craig Crews and Raymond Deshaies. However, interest in PROTACs did not pick up until 2015 when improved molecules were developed by the laboratories of Jay Bradner, Alessio Ciulli and Craig Crews. Ever since, PROTACs and the wider field of targeted protein degradation have expanded exponentially, with many groups around the world developing degraders as chemical tools to study proteins and as drug candidates for the treatment of diseases.